Optimalisasi Penerapan Digital Marketing Usaha Mikro, Kecil, dan Menengah GeOL (Getek Online) - Pane, Dewi Nurmasari; Sianipar, Hikmatul Fadhilah; Rahmadani, Rahmadani; Fikri, Miftah El (JPM: Jurnal Pengabdian Masyarakat, 2026)
While MSMEs play a vital role, they still face serious challenges, particularly in marketing. Many MSMEs in villages still rely on conventional methods to market their products, such as direct sales in traditional markets, word of mouth, or local marketing with very limited reach. This results in superior village products, such as Getek Online (GeOL), being unable to compete more broadly in regional or national markets. Various digital platforms such as social media (Instagram, Facebook, TikTok), marketplaces (Shopee, Tokopedia, Bukalapak), and e-commerce websites and applications provide significant opportunities for MSMEs to expand market reach and increase product competitiveness. Not only does it increase sales, digital marketing also helps businesses understand consumer behavior, build long-term relationships with customers, and increase promotional effectiveness at a relatively lower cost than conventional media. Responding to these challenges, the Getek Online (GeOL) initiative emerged, a community-based movement to digitalize the marketing of river crossings using crossing tools made from wood and bamboo, typical of Pematang Serai village. GeOL is a local innovation aimed at facilitating village MSMEs in utilizing digital marketing collectively and in a structured manner.